2020
DOI: 10.3390/rs12152396
|View full text |Cite
|
Sign up to set email alerts
|

InSAR Campaign Reveals Ongoing Displacement Trends at High Impact Sites of Thessaloniki and Chalkidiki, Greece

Abstract: We studied the broader area of Thessaloniki in northern Greece and Chalkidiki and performed an InSAR campaign to study the surface deformation phenomena that have been known to exist for at least two decades. Sentinel-1 data (2015–2019) together with drill measurements were exploited to focus on specific sites of interest. Our results indicate an ongoing displacement field. At the region of Kalochori and Sindos—where intense subsidence in the 1990s was previously found to have had a natural surface rebound in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…According to the InSAR Greece dataset, all the already-studied sites are continuing to deform. For instance, the Sindos-Kalochori region in the west of Thessaloniki [59][60][61][62][63][64] (Figure 10 (3, 4)), Anthemountas Basin in the east of Thessalonki [65] (Figure 10 (5)), Thriasio plain in the west of Athens [66] (Figure 10 (19)), and the Eastern Thessaly plain [67,68] (Figure 10 (6)) are some of the sites presenting a persistent deformation pattern identical to that already known.…”
Section: Insar Greece Product: Mapping Diverse Deformation Regimesmentioning
confidence: 90%
See 2 more Smart Citations
“…According to the InSAR Greece dataset, all the already-studied sites are continuing to deform. For instance, the Sindos-Kalochori region in the west of Thessaloniki [59][60][61][62][63][64] (Figure 10 (3, 4)), Anthemountas Basin in the east of Thessalonki [65] (Figure 10 (5)), Thriasio plain in the west of Athens [66] (Figure 10 (19)), and the Eastern Thessaly plain [67,68] (Figure 10 (6)) are some of the sites presenting a persistent deformation pattern identical to that already known.…”
Section: Insar Greece Product: Mapping Diverse Deformation Regimesmentioning
confidence: 90%
“…To cross-evaluate the InSAR Greece project's findings with ground truth data, the subsiding deformation pattern identified at the Sindos-Kalochori region was compared with ground water level contour maps for the same time period [64]. Ground truth techniques have been used several times to evaluate the subsiding patterns of this study area identified by the use of ERS 1, ERS 2, and ENVISAT datasets [61][62][63].…”
Section: Insar Greece Product: Mapping Diverse Deformation Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors mainly describe data capture technologies, data processing accuracy, and presentation methods. Data capture methods, as described by the authors, must also be feasible during airport operation [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The PSI results are an indication that water balance in the area might not have been restored after 2014, and that over-exploitation of Moudania watershed continues. This observation is also highlighted in Svigkas et al (2020), through an InSAR analysis from 2015 to 2019, validated by ground truth data.…”
Section: Changes In the Aquifer System Of Western Chalkidiki Regionmentioning
confidence: 57%